What Drives China's Growing Role in Africa? - Wang, Jian-Ye. (Washington, D.C. : International Monetary Fund, 2007)
What role does China play in Africa's development? What drives China's increasing economic involvement in the continent? This paper attempts to provide a quantified assessment of China's multifaceted influence as market, donor, financer and investor, and contractor and builder. Though in the past official development aid predominated, the paper argues that government policies, markets for each other's exports, Africa's demand for infrastructure, and differences in China's approach to financing have together moved commercial activities-trade and investment-to the center of China-Africa economic relations. While China's public sector, state financial institutions in particular, has been instrumental in the process, the influence of its private sector is increasing. Implications for the future of China-Africa economic relations are briefly noted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet